Investigating the interactional significance of the use of well by a child with ASD during writing interactions. (29th May 2022) - Maxwell, Jamie; Damico, Jack
Abstract : Background: Understanding the strategies children use to negotiate interactional breakdowns is important, as it can help clinicians to recognize, orient, and mediate the breakdowns collaboratively with the child, in order to re-establish intersubjectivity. In previous clinical and research contexts, one participant we observed evidenced many behaviors initially coded as 'avoidance' or 'failure to maintain topic' or as problematic in some way. These behaviors often contained specific linguistic devices (e.g., 'hmmm, ' 'bu:t, ' and 'well'). The functions of well as a discourse marker have been documented extensively by conversation analysts in neurotypical populations (e.g., Heritage, 2015; Kovarsky, 1990; Pomerantz, 1984; Schegloff and Lerner, 2009; Schiffrin, 1987). This study employs principles of conversation analysis (CA) to investigate the function of well in the clinical contexts observed. Method: Interactional analysis, a hybrid approach to CA, was employed to investigate one child's use of well in writing interactions. Data were collected over the course of one semester. Three sessions were chosen for analysis, transcribed, and analyzed for instances of well. Each occurrence was analyzed and coded individually. Thematic analysis followed, in order to arrive at an overall understanding of how the participant employed well interactionally. Results: Well in turn-initial places occurred 40 times across the three sessions. These instances could be organized into four different themes of use: issue with question posed; response may not meet listener expectations; difficulty formulating response; and loss of intersubjectivity. Discussion/conclusion: This analysis highlights how the participant's use of well in the interactions analyzed was meaningful. Turns prefaced by well signaled breakdowns in intersubjectivity, a need for conversational support, disagreement, issues with the previous speaker's turn, or a warning/acknowledgement that the response might be different than the listener's expectation. Clinical and research implications are explored.